Interferon‐γ decreases ATP‐binding cassette subfamily G member 1‐mediated cholesterol efflux through small ubiquitin‐like modifier/ubiquitin‐dependent liver X receptor‐α degradation in macrophages. (18th December 2020) - Dong, Mengya; Zhang, Yan; Xu, Chenbo; Wang, Chen; Liu, Mengping; Zhang, Zhanyi; Wu, Haoyu; Yuan, Zuyi; Zhou, Juan
Abstract: The effects of interferon‐γ (IFN‐γ) on cholesterol accumulation and the development of foam cells are still unclear. In the present study, we found that IFN‐γ promoted liver X receptor (LXR)‐α degradation through the ubiquitin–proteasome system in macrophages. The process was dependent on its interactions with phosphorylated signal transducer and activator of transcription 1 (p‐STAT1) and protein inhibitor of activated STAT 1 (PIAS1) because both fludarabine and PIAS1 shRNA reversed the decrease in LXR‐α protein expression induced by IFN‐γ. Additionally, IFN‐γ enhanced the interactions of ubiquitin‐conjugating enzyme 9 (UBC9), small ubiquitin‐like modifier (SUMO)‐1 and SUMO‐2/3 with LXR‐α. Moreover, treatment with shRNA specific for them not only reduced LXR‐α polyubiquitination but also reversed the IFN‐γ‐induced decrease in its expression. Two specific sumoylation sites in LXR‐α, K22 and K326, were indispensable for its IFN‐γ‐induced polyubiquitination because the K22R and K326R mutations inhibited the polyubiquitination and degradation of LXR‐α in IFN‐γ‐treated macrophages. In addition, K22R or K326R mutation almost completely restored ATP‐binding cassette subfamily G member 1 (ABCG1)‐mediated cholesterol efflux in IFN‐γ‐treated macrophages. Taken together, these findings indicate that IFN‐γ promotes LXR‐α degradation through a SUMO–ubiquitin‐dependent pathway, which may inhibit cholesterol efflux mediated by ABCG1 from macrophages and promote the development of atherosclerosis. Abstract : IFN‐γ decreases ABCG1‐mediated cholesterol efflux through SUMO/ubiquitin‐dependent LXR‐α degradation in macrophages.